Aesthetic Analysis Of Sustainable Design Principles in Modern Residential Interiors - Dina Kristiana Seftianingsih; Dian Muhammad Rifai; Nadila Dwi Koes Sumaningtyas; Marwahyudi Marwahyudi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze the application of sustainable principles in modern residential interior design and focuses on aesthetic aspects. With increasing attention to environmental sustainability issues, interior design plays an important role in reducing environmental impacts through the selection of environmentally friendly materials, efficient energy use, and space optimization. However, the aesthetic aspect cannot be separated from design, because it plays a role in creating visual comfort and occupant well-being. This study uses a qualitative descriptive method with an interdisciplinary approach, which includes literature reviews, design analysis, and case studies on several interior projects that have successfully combined sustainable and aesthetic principles. The results of the study show that interior design that considers sustainability not only focuses on energy efficiency and the selection of environmentally friendly materials, but also integrates aesthetic elements that enhance the comfort of the space. These findings emphasize the importance of public and designer awareness in creating functional, environmentally friendly, and aesthetic spaces. This study is expected to provide theoretical and practical contributions to the development of interior design that supports sustainability without sacrificing the aesthetic quality and comfort of the space.